2022
DOI: 10.1186/s43058-022-00322-1
|View full text |Cite
|
Sign up to set email alerts
|

Intervention, individual, and contextual determinants to high adherence to structured family-centered rounds: a national multi-site mixed methods study

Abstract: Background Effective communication in transitions between healthcare team members is associated with improved patient safety and experience through a clinically meaningful reduction in serious safety events. Family-centered rounds (FCR) can serve a critical role in interprofessional and patient-family communication. Despite widespread support, FCRs are not utilized consistently in many institutions. Structured FCR approaches may prove beneficial in increasing FCR use but should address organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…However, the poststudy qualitative analysis identified multiple barriers to implementation and adoption. Subsequently, as part of a larger dissemination and implementation study of PFC I‐PASS, known as the PFC I‐PASS Safer Communication on Rounds Everytime (SCORE) Study, 22 we conducted a baseline analysis of patient/family, nurse, and physician beliefs/attitudes, and self‐reported practices about FCR.…”
Section: Introductionmentioning
confidence: 99%
“…However, the poststudy qualitative analysis identified multiple barriers to implementation and adoption. Subsequently, as part of a larger dissemination and implementation study of PFC I‐PASS, known as the PFC I‐PASS Safer Communication on Rounds Everytime (SCORE) Study, 22 we conducted a baseline analysis of patient/family, nurse, and physician beliefs/attitudes, and self‐reported practices about FCR.…”
Section: Introductionmentioning
confidence: 99%